A New Method of Creating Technology/Function Matrix for Systematic Innovation without Expert - Tien-Yuan Cheng (Journal of Technology Management & Innovation, 2012)
The technology/function matrix is comprised by specific technologies and functions, and through the technology/function matrix we can known what the technologies with functions have opportunities for innovation of product or technology. However, the technology/function matrix is very difficult to create, because the patents need to be read, analyzed and categorized into the technology/function matrix always more than hundreds or thousands. In this research, I propose a method to create a technology/function matrix just need to execute patent search without reading and analyzing patents. Through the proposed method anyone can create a technology/function matrix in a short time without experts’ help even if there are thousands of thousands of patents need to be read and analyzed.